SARS-CoV-2 surrogate (Phi6) environmental persistence within free-living amoebae. (24th September 2021) - Dey, Rafik; Dlusskaya, Elena; Ashbolt, Nicholas J.
Abstract: The reported persistence of SARS-CoV-2 virions in aquatic environments highlights the need to better understand potential mechanisms that may prolong its dissemination. We evaluated the possibility that amoebae might serve as transport hosts by studying the interaction of the enveloped bacteriophage Phi6, as a potential surrogated along with one of the most common amoebae in engineered aquatic environments, Vermamoeba vermiformis . Using microscopy, imaging flow cytometry and bacteriophage cell culture, our results imply that the SARS-CoV-2 surrogate triggers amoebic mitochondria and induced apoptosis to promote viral persistence in trophozoites. Furthermore, virus-infected amoebae were still infectious after 2 months within FLA cysts. These results suggest that amoebae could contribute to the environmental persistence of SARS-CoV-2, including disinfection processes. In addition, amoebae could be a successful model system for understanding respiratory virus-eukaryotic biology at the cellular and molecular levels. HIGHLIGHTS: Amoebic mitochondria serve as a support organelle platform for the SARS-CoV-2 surrogate persistence. Long-term stability of RNA enveloped viruses in amoeba-forming cysts. Free-living amoebae as a potential vector and environmental reservoir for RNA enveloped viruses.